2004
DOI: 10.1152/ajpgi.00428.2003
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin production by human intestinal epithelial cells: a potential regulator of mucosal immune responses

Abstract: Receptor activator of NF-κB (RANK) and its ligand (RANKL) are important members of the TNF receptor (TNFR) and TNF superfamilies, respectively. RANK is expressed on osteoclasts, T-lymphocytes, and dendritic cells, and its ligation with RANKL leads to cellular activation. However, another member of the TNFR family, osteoprotegerin (OPG), acts as a decoy receptor, binding to RANKL and preventing its interaction with RANK. Furthermore, OPG also binds TNF-related apoptosis-inducing ligand (TRAIL), an important reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 48 publications
(63 reference statements)
0
43
0
Order By: Relevance
“…Previous studies have shown the utility of antiapoptotic molecules to extend the life of intestinal primary cells after detaching them from the intestinal tissue (14,23). Thus, here we added recombinant osteoprotegerin (OPG) during the transport of the tissue and immediately after PEC isolation to prevent anoikis, OPG is a tumor necrosis factor alpha receptor family member, which acts as a decoy by binding TRAIL and TRANCE, blunting the apoptosis pathway (24)(25)(26). We previously demonstrated that intestinal epithelial cells produce OPG in response to Cryptosporidium infection (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the utility of antiapoptotic molecules to extend the life of intestinal primary cells after detaching them from the intestinal tissue (14,23). Thus, here we added recombinant osteoprotegerin (OPG) during the transport of the tissue and immediately after PEC isolation to prevent anoikis, OPG is a tumor necrosis factor alpha receptor family member, which acts as a decoy by binding TRAIL and TRANCE, blunting the apoptosis pathway (24)(25)(26). We previously demonstrated that intestinal epithelial cells produce OPG in response to Cryptosporidium infection (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies have indicated an antiapoptotic function for OPG wherein OPG acts as a decoy receptor for TNF-related apoptosis-inducing ligand (TRAIL), which in cancer cells induces a death receptor pathway of apoptosis through the DR5 receptor (56,57). The functional antianoikis effect of OPG that was shown by restoration of OPG expression in NF-B-inactive cells suggests that TRAIL might be involved in the induction of anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…35 It can bind to TNF-related apoptosis-inducing ligand (TRAIL) and induce caspase-dependent apoptosis, especially in Th1 cells, which is supposed to be important to regulate the balance of Th1/Th2 in the development of the immune system in newborns. 36 Soluble CD14 (sCD14) Colostrum and breast milk contain high levels of the sCD14 molecule, exceeding the concentration found in the serum more than 20 times. 37 This component affects the modulation of innate and adaptive immune responses in the intestine during bacterial colonization and thus controls homeostasis in the newborn's intestine.…”
Section: α-Lactalbuminmentioning
confidence: 99%